A guideline for the strategic implementation of social media messaging within a marketing communication context - Ewoudt Cloete; Lida Holtzhausen (Communicare)
Marketing communication practitioners lack a guideline for implementing social media strategically. In the light of this, the authors of this article explored the strategic implementation of social media within a marketing communication context. A grounded theory process was firstly followed in order to compile a list of social media messaging categories. This list was then paired with the disciplines of the marketing communication mix, based on their inherent similarities. To demonstrate the practical relevance of the pairings thereafter, the authors followed a process of action research as a way of analysing an organisation’s existing social media messaging plan, referencing the strategic considerations that the pairing process inferred. By doing so, the authors established that the pairing and action research process explored could be used as a strategic guideline for social media managers to improve the degree to which an organisation’s social media messaging is conducive to the reaching of specific marketing communication objectives.